Progress in Treatment of Anal Fissure with Traditional Chinese and Western Medicine - Ma, Zhiyu; Liang, Jinghua (Journal of Contemporary Medical Practice, 2025)
Anal fissure is a common disease in anorectal surgery, mainly for pain, bleeding, anal spasm. The specific etiology of anal fissure is still unclear. How to choose a reasonable treatment to alleviate the pain and improve the quality of life of patients is a difficult problem. In this paper, in recent years, the study of anal fissure at home and abroad were briefly summarized to traditional Chinese medicine treatment, western medicine treatment for reference.